The study of socialization of "respect" behaviors as reported by adolescents - Dalida, Monique Pascual (College of Home Economics, University of the Philiuppines Diliman, 2010)
ABSTRACT This study aims to describe how Filipino parents socialize "respect" behaviors as reported by their adolescent children. Moreover, it seeks to identify which "respect" behaviors are taught by parent, what strategies they use to teach these behaviors, and the effects of the socializing approaches to the parent-child relationship. Through purposive sampling in two universities in Quezon City, the study was able to gather 112 adolescents who accomplished the "Respect" Behavior Questionnaire and participated in focus group discussions. Frequency distribution tables revealed that among the different "respect" behaviors, pagmamano, saying po and opo, and rightfully addressing elders are taught by most parents, while behaviors of obedience and submissiveness received low reports of being socialized. Low-power strategies, such as reminding and explaining, and modeling were found to be the most preferred approaches by parents and adolescents. Other socializing approaches such as nagging, use of severe punishment, and not practicing what they teach can cause conflict in the parent-adolescent relationship. The current study suggests that the family, specifically the parents still have the greatest role in teaching "respect" behaviors, and that Filipino parents are changing their ways of instilling these behaviors to their children. Social institutions may provide assistance to parents by acknowledging their role in parenting and by enlightening them on the different ways of teaching "respect" behaviors to their children. Further studies may explore on the shift in the socialization process that exist between parents and adolescents in order to better describe today's Filipino family.